Valor nutricional de silagem de capim-mombaça com aditivos agroindustriais - Oliveira, Euclides Reuter de; Moncao, Flavio Pinto [UNESP]; Moura, Lais Valenzuela; Araujo Gabriel, Andrea Maria de; Tonissi e Buschinelli de Goes, Rafael Henrique de; Lempp, Beatriz; Nascimento, Felipe de Almeida (Univ Estadual Londrina, 2014)
It was aimed to evaluate the chemical composition of grass silage-mombasa associated with different additives in four times of opening the silo. The experiment was conducted in UFGD. After harvesting the forage, biomass in natura crushed, was taken to the lab, homogenized and enriched on the basis of natural mass, with the following additives: 5% wheat bran, 5% of waste (broken grain and soy ice cream cone) of soybean, 5% urea in natural matter and the witness (without additive). The silos were opened after (unprocessed material), 15, 30 and 45 days, for the analysis of chemical composition. The data obtained were analyzed through the statistical programme SISVAR and averages were compared to 5% of probability, by Skott-Knot. The grass silage-mombasa without additive presented major (P<0.05) dry matter content compared to other treatments at time 0 and 30 days of silage and did not differ (P>0.05) of grass silage- mombasa associated with 5 of urea in 15 days and 45 of silage. The grass silage-mombasa with 5% urea showed the highest crude protein content at time 0 and differed from other treatments. The silage of mombasa associated with 5% urea provided greater in vitro digestibility of dry matter to 15 days of silage.
Nutritional value of grass silage of mombasa associated with additives agroindustrial
Keywords: Animal nutrition; conservation of forage; nutritional value; panicum maximum